Human-Centered Explainable Artificial Intelligence - Mollaei, Nafiseh (2022)
This work was partly supported by science and technology foundation (FCT), under projects OPERATOR (ref. 04/SI/2019) and PREVOCUPAI (DSAIPA/AI/0105/2019), and Ph.D. grants PD/BDE/142816/2018 and PD/BDE/142973/2018.